Glitch, the Post-digital Aesthetic of Failure and Twenty-First-Century Media. (February 2023) - Kemper, Jakko
This paper aims to understand how everyday life is affected by new technological conditions through an inquiry into glitch, a concept that signifies moments of faulty interference in the regular operation of a technology and that is often labeled a ghost in the machine. By drawing on two concepts from cultural studies – spectrality and post-digital culture – it demonstrates how the imperfection-oriented aesthetic of glitch is today complicated by the technological tendency to bypass human awareness. By developing this argument through a reading of German electronic music group Oval's influential glitch-based record 94diskont (1995), the paper shows how glitch's signification of mediation, fragility and technological complexity has been modulated in recent years. This analysis is augmented through a consideration of Mark B.N. Hansen's concept of 'twenty-first-century media', which takes as highly significant the tendency of contemporary media to operate beyond the thresholds of human cognition and perception. The paper suggests that, as a result of these new medial forms, the subversive potential of glitch-based artworks is impacted severely, but also that glitch's status of ghost in the machine offers valuable resources for thinking through the media experiences afforded by 21st-century media. This paper thereby points to new potential modes of critique, and expands existing cultural debates about aesthetics, technology, and the constitution of everyday life.